Psychiatry and COVID-19: putting our best foot forward. (August 2020) - Strous, Rael D.; Gold, Azgad
Summary: COVID-19 presents new challenges for psychiatry as clinical management, ethical dilemmas and administrative complications need to be addressed. The psychiatrist should protect the needs and rights of the mentally ill while maximising population health and ensuring solidarity, reciprocity and community well-being for all.